PANCASILA: AZAS DEMOKRASI BERKARAKTER INDONESIA - Moh. Miftahusyaian (el-hikmah, 2012)
The greatest assignment for all elements in this country is to bridge the gap between democratic ideals that emerged and broached by the founding fathers and with the current real life situation of Indonesian democracy with enormous number of problems. The ideal and elegant of democratic aspiration - as stated in the Pancasila – is in contrast with the real conditions of contemporary democracy that bloated with egoistic conflicts of interest and social mess. Yet, Pancasila calls for democracy - through mass consultative mechanisms – directed to bring out social justice for all Indonesian people. This paper attempts to disclose the discourse about how democracy should be taught and deployed within the Indonesianism frame. It worth to be put forward because Indonesian has a particularly different current of history and cultural mold in comparison to other countries. Therefore, the interpretation and implementation of democracy must be re-investigated and re-explored from the history and culture of Indonesia itself, rather than taken for granted taken from the foreign cultures-mainly Western-which may not be compatible with the Indonesian characteristics. With deep understanding, the actual values ​​of democracy by Indonesian characterized, recorded on the precepts contained in the Pancasila markedly. Each precept of the Pancasila is core characteristic of cultural values of every ethnic groups in Indonesia. This is initiated in order to enlive Pancasila and turn every action in the name of nation and state.